Mechanism and Prevention and Control of Mine Earthquake in Thick and Hard Rock Strata considering the Horizontal Stress Evolution of Stope - Ming Zhang; Xuelong Hu; Hongtao Huang; Guangyao Chen; Shan Gao; Chao Liu; Lihua Tian (Shock and Vibration)
This study investigated the mechanism, prevention measures, and control methods for earthquake disasters typically occurring in mines with thick and hard rock strata. A mine stope with large faults and thick hard rock strata in Hebei Province was taken as the background study object. Then, theoretical analysis and numerical simulation methods were adopted in conjunction with field monitoring to explore how horizontal stress evolves in the thick and hard hanging roofs of such mines, potentially leading to mining earthquakes. Then, based on the obtained results, a mining design method was proposed to reduce the horizontal stress levels of earthquake mitigation. The results showed that, under the control of large faults, semiopen and semiclosed stopes with thick hard rock strata are formed, which cause influentially pressurized and depressurized zones during the evolution of the overburden movements and horizontal stress. It was determined that the stress concentrations mainly originated from the release and transfer of horizontal stress during the rock fractures and movements in the roof areas, which were calculated using a theoretical estimation model. The horizontal stress concentrations formed “counter torques” at both ends of the thick and hard strata, which prevented the support ending due to tensile failures. As a result, the limit spans were increased. This study proposed a mining strategy of using narrow working faces, strip mining processes, and reasonable mining speeds, which could effectively reduce horizontal stress concentrations and consequently prevent and control mining earthquakes. This study’s research results were successfully applied to the mining practices in working face 16103.